Creativity as a development motivator. The case of San Cristobal de las Casas, Chiapas, and the declaration of creative city for the crafts and folk art by UNESCO - Solórzano Gil, Mónica (2017)
This paper presents an analysis of the potential of the city of San Cristobal de Las Casas and the Altos de Chiapas region to take advantage of the various resources and creative inputs derived from its rich cultural tradition as motivator of economic development. Part of the analysis included here is derived from the application project the city has promoted since 2013 in order to join the UNESCO Creative Cities Network of Craft and Folk Art. In 2015 the city became the first in Mexico to join this network. This is an unprecedented challenge for Mexico and highlights the opportunity to use its creativity to generate substantial changes in the quality of life of its inhabitants using its own resources in a sustainable way.